2018
DOI: 10.22159/ajpcr.2018.v11i2.22783
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the Homozygous C.144DELC Mutation in Aurkc Gene in Algerian Infertile Men

Abstract: Objective: Male infertility is a major health problem worldwide. Despite recent advances, the etiopathogenesis of spermatogenic failure remains largely uncertain. Aurora kinases, a family of serine/threonine kinases, consisting of Aurora A (AURKA), Aurora B (AURKB), and Aurora C (AURKC), are essential kinases for cell division through regulating mitosis and meiosis. The aim of this study was to investigate the frequency of c.144delC mutation in AURKC gene in infertile Algerian patients with abnormal sperm para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A study by Ghédir et al reported that approximately 80% of infertile men with macrozoospermia were homozygous for a mutation on the AURKC gene (c.144delC) in the population of Tunisia (16). However, in a study by Larbi et al, no mutations on the AURKC gene were noted in Algerian men with infertility (19). These results demonstrated that the molecular analysis of the AURKC gene in infertile men is key for the efficient management of reproduction problems in men.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ghédir et al reported that approximately 80% of infertile men with macrozoospermia were homozygous for a mutation on the AURKC gene (c.144delC) in the population of Tunisia (16). However, in a study by Larbi et al, no mutations on the AURKC gene were noted in Algerian men with infertility (19). These results demonstrated that the molecular analysis of the AURKC gene in infertile men is key for the efficient management of reproduction problems in men.…”
Section: Discussionmentioning
confidence: 99%